Determining Electrochemical Surface Stress of Single Nanowires. (12th January 2017) - Wang, Hui; Shan, Xiaonan; Yu, Hui; Wang, Yan; Schmickler, Wolfgang; Chen, Hong‐Yuan; Tao, Nongjian
Abstract: Electrochemical surface stress is important in nanomaterials because of their large surface‐to‐volume ratios, which lead to unique mechanical and electrocatalytic properties, but directly measuring this quantity has been challenging. Here we report on experimental determination of the surface stress, and associated electrochemical processes of a single gold nanowire with an optical imaging technique. We show that surface stress changes linearly and reversibly with the potential between 0 and 0.8 V versus Ag/AgCl, but abruptly with large hysteresis, associated with the oxidation and reduction of the nanowire, between 0.8 and 1.5 V. The potential derivative of the surface stress closely resembles the cyclic voltammograms. We described the observations in terms of anion adsorption and surface oxidation/reduction. This work demonstrates a new approach to study electrochemical processes and the associated surface stress changes of nanomaterials.